PENYEBARAN SERBUK SARI DAN KERAGAMAN GENETIK BIJI YANG DIHASILKAN KEBUN BENIH Pinus merkusii DI JEMBER - I. L. G. Nurtjahjaningsih (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Pollen movement is a critical determinant in population genetic, plays important role in forest tree improvement and conservation genetic. This study was conducted to understand physical pollen movement and to determine seasonal genetic diversity of seed crops in a seedling seed orchard (SSO) of Pinus merkusii, located at Jember, East Java. Physical pollen movements were measured using 25 pollen traps conducted at three flowering seasons i.e. August 2005, November 2005 and March 2006. For offspring populations, seeds were collected at June, September and December that represented mating in each pollen observation season. Then, genetic diversity of the seed crops were analyzed using five microsatellites markers for P. merkusii. Results showed that number of pollen grains was significantly difference among seasons, but insignificant to both trap locations and interaction season-trap locations. The trapped pollen number was low in both August and March, but it was abundant in November. Value of gene diversity of offspring was highest in August (HE = 0.402) compared to other seasons. This study showed that physical pollen movement in the SSO might synchronize, however level of the HE varied among seasons. Seasonal variation in mating status was briefly discussed.